PENGARUH PENYAJIAN VISUAL DAN GAYA BAHASA PADA VIDEO TENTANG PARIWISATA DI KABUPATEN GARUT TERHADAP PENINGKATAN PENGETAHUAN - Saleh, A.; Nirwana, Testa Pradia; Matindas, Krishnarini; Gustina, Anna (PROSIDING KOMUNIKASI)
Tourism is one of sector that is much interested by the world community, this demand has increased every year. Garut is one of the districts in West Java which is interested by tourists. Promotion in marketing the tourism product is very important for the development of communities and regions. The promotion can use media of video through social media to provide an illustration and a knowledge of tourism, and convince these young travelers to visit the tourist attractions that is offered. The purpose of this study were 1) to test the effect of visual presentation and style of language through video to increase student knowledge, 2) to analyze the message combination of the most effective on the media video about tourism in Garut. This research used true experimental methods with 2 x 2 factorial design and use pretest posttest control group design. Factors is used in the visual presentation consists of photos and infographics, and the language style consists of formal and conversational. Subjects were 75 students of the Bogor Agricultural Institute. The results showed that the visual presentation and language style through videos significant effect on the improvement of knowledge, the whole combination treatment was not significantly different to the increase of knowledge. Keywords: improvement knowledge, language style, video tourism, visual presentation PENDAHULUAN